2008
DOI: 10.1016/j.ccc.2007.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cerebral Injury from Cardiac Surgery

Abstract: Cerebral injury is a frequent complication of cardiac surgery and has been associated with high mortality, morbidity, hospital costs, and an increased likelihood of admission to a secondary care facility after hospital discharge, and impaired quality of life. 47,71,78,86 There are a variety of manifestations of perioperative cerebral injury including ischemic (or, less commonly, hemorrhagic) stroke that occurs in 1.5% to 5.2% of patients, encephalopathy affecting 8.4% to 32% of patients, and neurocognitive dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 96 publications
0
65
0
4
Order By: Relevance
“…Cardiopulmonary bypass may result in stroke by systemic hypotension and diffuse embolization of fibrin or gaseous material as demonstrated by transcranial Doppler ultrasonography. 29,30 The majority of strokes are recognized within 48 hours of surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiopulmonary bypass may result in stroke by systemic hypotension and diffuse embolization of fibrin or gaseous material as demonstrated by transcranial Doppler ultrasonography. 29,30 The majority of strokes are recognized within 48 hours of surgery.…”
Section: Resultsmentioning
confidence: 99%
“…30 While some reports have indicated that statins are associated with a reduced incidence of atrial fibrillation after CABG, 31 it has not been clearly Values are mean Ϯ SD or %. ACE ϭ angiotensin converting enzyme; CABG ϭ coronary artery bypass grafting.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies [6,8,9,21], the causative mechanisms and risk factors for perioperative strokes in patients undergoing CABG were determined. The incidence of postoperative stroke correlates mainly with the adverse effect of cardiopulmonary bypass due to large numbers of microemboli built by fragments of atheromatous plaques from the ascending aorta, thrombi, platelets, destroyed red blood cells, white blood cells, lipids, and gas [11,13,22].…”
Section: Discussionmentioning
confidence: 99%
“…As opposed to TAVR, cardiac surgery involves a wide spectrum of neurological injuries, including ischemic stroke, encephalopathy, and neurocognitive decline. 38 Embolism is considered the main mechanism of neurological injury, 39 and embolic material released into the cerebral circulation has been detected during various aortic manipulations performed in cardiac surgery. 40 Similar to TAVR patients, an increased risk of silent CNS infarction related to cognitive decline has been reported for cardiac surgery patients.…”
Section: Cardiac Surgery Perspectivementioning
confidence: 99%